An Analysis of Hots in the 5th Grade Elementary School Students’ Learning with Radec Model with the Theme of "Electricity Around Us" - Lestari, Anggi; Suhandi, Andi (International Conference on Elementary Education, 2020)
The importance of teaching students the ability to think that is trained early is an obligation of teachers in educational innovation. One of them is developing Higher Order Thinking Skills (HOTS). This study aimed to analyze the ability of students to work on HOTS questions in learning with the RADEC model which is one of the innovative models that is able to train students’ ability to think at a higher level. This research used descriptive method with a qualitative approach. The research subjects were 24 fifth grade elementary school students of Babakan Trogong, Bandung. The data was collected by using HOTS-questions instrument, observation sheets when learning took place, and the data processed in a descriptive manner. The results of this study indicated that RADEC learning model helped students do HOTS questions with the finding that 19 out of 24 students experienced an increase in learning outcomes